JM-20 como composto multialvo: avaliação do potencial antioxidante, inibidor de colinesterases e citotoxicidade - Silva, Fernanda D’Avila da (2020)
Multi-target compounds have aroused the interest of many researchers. The main characteristic of these substances is the ability to act through different mechanisms of action, a relevant fact in cases of pathologies caused by multiple causes. In this context, in some cases of neurodegenerative diseases, a neuronal loss may occur in certain brain regions that contain cholinergic neurons, consequently causing impairment of cognitive functions. Oxidative stress is characterized by the imbalance between the production of reactive species and antioxidant defenses and can be directly related to the causes or consequences of pathologies related to the CNS. Previous studies have shown that JM-20, 1,5-benzodiazepine fused to a dihydropyridine fraction, has different pharmacological properties of clinical interest. In this sense, the main objective of this study was to evaluate the effect of JM-20 on AChE and BChE from different sources, identify the type of enzyme inhibition and understand the interactions between the compound and the enzymes using silicon molecular docking tools. Besides, to verify the protective effect on oxidative stress induced by Fe2+ in leukocytes and to determine the scavenger activity of free radicals. Likewise, investigate possible cytotoxicity using human blood cells and predict ADMET parameters using in silico virtual screening tools. The BChE used was purified from Equus ferus and present in human plasma, while AChE was from Electrophorus electricus, total erythrocytes and present in membranes isolated from human erythrocytes (ghost). The enzymes were pre-incubated for 30 minutes in the presence of different concentrations of JM-20 (1 nM - 200 μM). To assess the type of enzyme inhibition, a kinetic study was performed varying the concentration of the substrate (0.05 - 1.6 mM). Human blood was obtained from healthy volunteers. Immediately after blood collection, the leukocytes or erythrocytes were isolated, washed, and treated with different concentrations of JM-20 and evaluated according to each specific test. The results demonstrated the potential inhibitory effect on AChE activity. These effects were observed in all enzymes tested (IC50 = 123 nM ± 0.2 for E. electricus, 172 nM ± 0.2 for total erythrocytes and 158 nM ± 0.1 for ghost). Besides, we suggest that the compound has a mixed type of inhibition as it changes the Km and Vmax of AChE. Molecular docking demonstrated the existence of eight different isomers of JM-20, and the 4R isomers interact better with HsAChE. The TBARS result points to a potent antioxidant and scavenger effect of free radicals seen in the slow phase of the reaction. However, exposure to all tested JM-20 concentrations (10-50 μM) caused a significant increase in the levels of reactive intracellular species (RS). Although decreased cell viability and increased RS production have been observed, exposure to JM-20 (10-50 μM) did not alter the cell cycle, nor did it cause hemolysis. Analyzes of virtual screening of the JM-20 demonstrated a similar ADMET profile to nifedipine. Thus, our findings support the potential clinical use of JM-20, for the treatment of pathologies associated with the CNS.